A hybrid H2O/IL absorption and CO2 compression air-source heat pump for ultra-low ambient temperatures. (15th January 2022) - Wu, Wei; Zhai, Chong; Huang, Si-Min; Sui, Yunren; Sui, Zengguang; Ding, Zhixiong
Abstract: Heat pumps are promising for carbon neutrality. However, the existing vapor-compression heat pumps suffer from severe performance deterioration while the absorption heat pumps rely on toxic NH3 -based fluids in sub-zero conditions. Therefore, a novel hybrid H2 O/ionic liquid absorption and CO2 compression air-source heat pump is proposed for ultra-low ambient temperatures. The verified property and cycle models are used for performance optimization, characterization, and comparison. The coupling temperature that oppositely affects the efficiencies of the two sub-cycles is optimized to be 6 °C. With the ambient temperature rising from −30 °C to 0 °C, the primary energy efficiency (PEE) increases from 1.064 to 1.256, higher by 18–40% compared to a gas boiler. The heating capacity stably ranges in 94.0–102.9 kW, significantly increasing the reliability in cold climate. As the driving temperature rises from 96 °C to 130 °C, the PEE slightly varies in 1.155–1.190, while the exergetic coefficient of performance decreases from 0.609 to 0.600, encouraging the use of low-temperature heat sources (e.g., 100 °C). Compared to existing heat pumps, the hybrid heat pump efficiently operates at −30 °C, showing the highest PEE for most sub-zero conditions with much slower heating capacity deterioration. The advantage is much higher under colder conditions. Highlights: A hybrid absorption-compression air-source heat pump proposed for ultra-low temperature. H2 O/ionic liquid and CO2 are used to minimize the toxicity, crystallization, and GWP. The optimal coupling temperature is 6 °C to maximize the integrated energy efficiency. Efficiency higher by 18–40% at various ambient and driving temperatures in cold climate. Hybrid heat pump efficiently operates at −30 °C, with the best efficiency and stability.